Measurement of photoplethysmography signal for heart rate variability and comparison of two different age groups - Shah, Mansoor Hussain; Khan, Sheroz; Sidek, Khairul Azami; Kazmi, Syed Absar; Abdul Kadir, Kushsairy (IEEE, 2015)
This paper investigates to compare the Photoplythsmography (PPG) signals based on Heart Rate Variability (HRV) criteria for two different age groups. This paper demonstrates the variation of PPG and HRV signals for subjects of age group in the twenties and fifties. The so used Easy Pulse Sensor module making use of the photo sensing technique to collect the amount of infra red light passing through the respective body part (finger tip in this case). After processing this signal through a series of condition stages involving low pass and high pass filter, a noise free PPG signal of adequate level is produced. The shape, frequency components and amplitude of this PPG signal depend upon the physiological condition as well age. This signal is then further processed by using the Arduino based processing board for being interfaced to a PC for display on the Graphical User Interface (GUI). The results are clear indicative of the physical conditions and age groups.